The Determinants of Bank Default Risk: Evidence from Commercial Banks in Euro Area under the Background of Brexit Referendum - LI, Jingchao (2018)
This study aims to find the determinants of bank default risk in the eurozone under the special period of Brexit referendum, and find how Brexit referendum affect the bank stability within a short term. The period of 2013-2017 is selected, whereas the largest 200 commercial banks in the euro area are chosen as the research sample. In the empirical analysis, The Boyd and Graham’s (1986) Z-Score is applied as the proxy for bank default risk, whereas bank specific variables, traditional macro level indicators and Brexit referendum related variables are considered as regressors in the panel data model. The result found that bank profitability, asset liquidity, capital adequacy, size and GDP growth are significantly and positively related with bank stability, whereas unemployment rate and inflation rate have negative impact on the bank Z-score. In addition, the short-term impact of Brexit referendum is tested to have negative impact on bank stability via the application of time dummy variables and Brexit referendum related financial variables, which indicates euro area banks are required to predict these political events accurately and make sufficient preparation before.